2013
DOI: 10.1167/iovs.13-12108
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Related and System-Related Barriers to Glaucoma Follow-up in a County Hospital Population

Abstract: Understanding patient-reported barriers to glaucoma follow-up and their variation based on ethnicity may give providers insight as to why patients do not adhere to follow-up recommendations. Strategies to improve follow-up may include reduced clinic wait times, simplified appointment scheduling, and provision of appropriate education and counseling regardless of the patient's native language and ethnicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 25 publications
0
33
0
Order By: Relevance
“…Previous research has shown that this population is less likely than other patient groups to obtain ocular examinations from an ophthalmologist. [32][33][34][35] The bilateral strategy ensures these patients receive treatment for both eyes when necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that this population is less likely than other patient groups to obtain ocular examinations from an ophthalmologist. [32][33][34][35] The bilateral strategy ensures these patients receive treatment for both eyes when necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Patient wait time results from pressures on provider time, and clinic inefficiencies cause excessive patient wait times, which in turn cause decreased patient satisfaction and barriers to health care. 7,8 Studying clinic workflow is a critical way to gain insight for improvements, but requires large quantities of detailed timing data because of the inherent variability of clinic activities. Time-motion methods can provide data about clinic workflows, but are resource-intensive and prohibitive for large-scale studies.…”
Section: Introductionmentioning
confidence: 99%
“… 14 , 15 , 33 Among these, poor follow-up adherence rates were highest among African-Americans, subjects aged 50–80 years, and those diagnosed with advanced stages of glaucoma. 10 – 12 , 15 , 16 One of these studies included: a community-based eye screening program in Baltimore, supported by Hoffberger Family Philanthropies, which targeted a high-risk population similar to that found in our present study. 9 The Hoffberger Program conducted community-based glaucoma screening examinations with a 59% rate of nonadherence to their follow-up visit.…”
Section: Discussionmentioning
confidence: 93%
“… 10 – 13 Other factors associated with poor follow-up adherence, especially among the underserved, include poor health literacy and difficulty navigating the complex healthcare system. 11 , 12 , 14 , 15 In previous studies, patients self-reported that a lack of transportation, difficulty affording copayment, uncertainty of where to find an ophthalmologist, a busy schedule, fear of an ocular diagnosis, and fear of treatment were all barriers to obtaining regular glaucoma-related eye examinations. 3 , 8 , 9 , 11 , 12 , 14 – 16 Research has suggested many strategies to improve patient adherence, but one of the most promising options involves the addition of a dedicated healthcare worker to help and encourage patients to attend eye examination appointments.…”
Section: Introductionmentioning
confidence: 99%